2012
DOI: 10.1111/j.1365-2672.2012.05345.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated dead-end ultrafiltration of large volume water samples to enable detection of low-level targets and reduce sample variability

Abstract: Aims: A Portable Multi-use Automated Concentration System (PMACS) concentrates micro-organisms from large volumes of water through automated dead-end ultrafiltration and backflushing. The ability to detect microbial targets from ground, surface and cooling tower waters collected using standard methods was compared with samples from the PMACS in this study. Methods and Results: PMACS (100 l) and standard grab samples (100-500 ml) were collected from sites in Florida and South Carolina, USA. Samples were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
(34 reference statements)
2
10
0
Order By: Relevance
“…A dead-end concentrator was designed for sampling recreational waters (40) and is commercially available (IntelliSense Design, Inc., Tampa, FL). A manual UF system (41) that operates on the same principle as the automatic UF but without a computer-controlled system worked well in recovering pathogens from 100-liter samples during field studies at Great Lakes and inland lake beaches (data not shown).…”
Section: Filters For Concentrating Microorganisms In Lake Watermentioning
confidence: 99%
“…A dead-end concentrator was designed for sampling recreational waters (40) and is commercially available (IntelliSense Design, Inc., Tampa, FL). A manual UF system (41) that operates on the same principle as the automatic UF but without a computer-controlled system worked well in recovering pathogens from 100-liter samples during field studies at Great Lakes and inland lake beaches (data not shown).…”
Section: Filters For Concentrating Microorganisms In Lake Watermentioning
confidence: 99%
“…Flow rate and pre-and postfilter pressures were monitored during filtration. The PMACS automated recovery cycle was then initiated to recover the material collected on the filter: 0.01% sodium polyphosphate in 0.1 M sodium phosphate buffer (PB-NaPP) (23,27,29) was pumped into the filter in the direction opposite to the forward flow (back flushed) to generate approximately 400 ml of retentate. The retentate was collected in a sterile polystyrene bottle and measured using a sterile 500-ml graduated cylinder.…”
Section: ) Masterflex Iip High-performance Pump Head On a Masterflexmentioning
confidence: 99%
“…The PMACS was cleaned after each inoculated wash trial by installing a dedicated cleaning filter and initiating the automated cleaning cycle: 2 to 4 liters of acidified (pH 6.0) solution with 540 ppm of sodium hypochlorite were pumped in the forwardflow direction through the inlet path and sample collection lines (27,29). The cleaning solution was then recirculated through the system for 20 to 30 min, followed by recirculation of a 0.1% sodium thiosulfate solution to neutralize residual sodium hypochlorite.…”
Section: ) Masterflex Iip High-performance Pump Head On a Masterflexmentioning
confidence: 99%
See 2 more Smart Citations